Impact of Dividend Policy on Earnings Management and The Moderating Effect of The Board of Directors and The Audit Committees: The French Case - Salah, Olfa Ben; Jarboui, Anis (Accounting and management information systems, 2023)
Research Question- To what extent can governance mechanisms (audit committee and board of directors) affect the relationship between dividend policy and earnings management? Motivation- The majority of the literature has showed that dividend policy can influence earnings management. However, the empirical results did not lead to the same results. Our study seeks to fill this gap by examining whether this impact can vary by taking into account certain moderating variables such as: the size of the board of directors, the number of board meetings, the independence and expertise of the members of the audit committees. Idea- This study examines the moderating effect of certain variables related to the effectiveness of the board of directors and the audit committee on the impact of the dividend policy on earnings management. Data- The authors selected French non-financial companies listed on the CAC All Tradable index during the 2008-2015 period. Tools- To test study's hypotheses, the authors applied linear regression with a panel data using the datastream database. Generalized least squares method is used to estimate the models. Findings- The results of this study show that the effect of the dividend policy on earnings management is more favorable in the case of companies where the board of directors is large. Contribution- This study shows that dividend policy constitutes an objective of earnings management especially in the companies with boards made up of a large number of directors. Investors and academics have an interest in better understanding the concepts: dividend policy and earnings management because the debates relating to these two variables have always been the subject of controversy. Thus, they can refer to corporate dividend policy as a mechanism for assessing the authenticity of corporate financial reports.